POTENTIAL MEDICINAL PLANTS "THE HIDDEN PARADISE" OLELE VILLAGE KABILA BONE DISTRICT AS ECOTOURISM SUPPORT - Moh. Gifari Hi Sahada; Jusna Ahmad; Abubakar Sidik Katili (Jambura Edu Biosfer Journal, 2022)
Olele  Village  is  a  village  with  quite  high  tourism  potential,  one  of  which  is  medicinal  plants  which  are  quite  high  and  varied.  This  study  aims  to  identify  species  of  medicinal  plants  in  this  village  and  identify  their  potential  as  ecotourism  support.  The  research  was  conducted  using  an  in-depth  interview  technique  with  a  qualitative  type.  The  data  obtained  will  then  be  documented  and  identified  using  the  book  and  the  Plant-Net  application.  The  results  showed  that  17  species  of  medicinal  plants  were  identified  from  the  results  of  interviews,  then  validation  was  carried  out  on  tourists  who  were  in  the  village  to  find  out  the  personal  interests  of  each  tourist. The development of tourist areas has also been responded positively by the community and local government